Analysis of the Suez Canal blockage with queueing theory - Johannes Gast; Tom Binsfeld; Francesca Marsili; Carlos Jahn (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The Suez Canal blockage in March 2021 delayed around USD 9.6bn of trade each day. The delay affected more than 400 vessels and likely disrupted further Supply Chain and transport operations even after clearing the blockage. Methodology: The model of this paper has two goals: first, predicting how long the queued-up vessels need to wait until continuing their voyage; second, at what time the entire queue resolves, and a new service cycle continues with steady-state behaviour. Findings: The model predicted that the queued vessels' behaviour, i.e., that the last ship will pass the canal five days after the clearing, which equals the number reported by the Suez Canal Authorities. AIS-data can further validate the model's input and output. The discussed model supports the decision-making processes by proving the tool to assess at what time circumventing the blockage is more beneficial. Originality: Supply Chain Management literature already established models from Queueing Theory to evaluate the efficiency of services and infrastructure. However, the literature does not use queueing models to assess Supply Chain risk. This research introduces a queueing model to Supply Chain Risk Management to analyse the recovery of a disrupted transport route, thereby forecasting delays caused by disrupted transport routes.
urn:nbn:de:gbv:830-882.0161795; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security